Biodiversity and threatened species reporting by the top Fortune Global companies. Issue 3 (19th March 2018) - Adler, Ralph; Mansi, Mansi; Pandey, Rakesh
Abstract : Purpose: The purpose of this paper is to explore the biodiversity and threatened species reporting of the top 150 Fortune Global companies. The paper has two main objectives: to explore the extent to which the top 150 Fortune Global companies disclose information about their biodiversity and species conservation practices, and to explore the effects of biodiversity partners and industry on companies' biodiversity and threatened species reporting. Design/methodology/approach: The study's sample is the top 150 Fortune Global companies. Each company's fiscal year ending 2014 annual report, its 2014 sustainability report, and its company website were content analyzed for evidence of biodiversity and threatened species reporting. This content analysis is supplemented by a detailed analysis that focusses on the sample's top five reporters, including a phone interview with a senior sustainability manager working at one of these companies. Finally, a regression analysis was conducted to examine the associations between companies' biodiversity and threatened species reporting and the presence/absence of biodiversity partners and a company's industry F&C Asset Management industry category. Findings: The reporting on biodiversity and threatened species by the top 150 Fortune Global companies is quite limited. Few companies (less than 15) are providing any substantial reporting. It was further observed that even among the high scoring companies there is a lack of consistent reporting across all index items. A subsequent empirical examination of these companies' disclosures on biodiversity and threatened species showed a statistically positive association between the amount of reporting and companies' holding of biodiversity partnerships. It was also observed that firms categorized as red- and green-zone companies made more disclosures on biodiversity and threatened species than amber-zone companies. Originality/value: This is the first study to systematically analyze corporate disclosures related to threatened species and habitats. While some prior studies have included the concept of biodiversity when analyzing organizations' environmental disclosures, they have done so by examining it as one general category out of many further categories for investigating organizations' environmental reporting. In the present study, the focus is on the specific contents of biodiversity disclosures. As such, this study has the twin research objectives of seeking to illuminate the current state of biodiversity and threatened species reporting by the world's largest multinationals and provide an appreciation for how certain organizational and industry variables serve to influence these reporting practices. These multiple insights offer companies, and potentially regulators, understanding about how to include (or extend) disclosures on biodiversity loss and species under threat of extinction.